Mediating Role of Social Problem-Solving on the Relationship be-tween Autistic Traits and Depression in a Non-Clinical Iranian Sample - Zahra Salehzadeh Einabad; Mahshid Mojtahedzadeh; Elaheh Khalili; Barbara Dristchel; Bijan Pirnia (Tehran University of Medical Sciences, 2022)
Background: Research on the role of social problem-solving in the relationship between autistic traits and depression is still in its nascent stage and more detailed research is required. Methods: We aimed to investigate the mediating role of problem-solving in the relationship between autistic traits and depression. A sample of 376 university students were assessed on depression, problem-solving and autism-spectrum quotient in 2019 at Shahed University, Tehran, Iran. Results: Social problem-solving played the role of a partial mediator in the relationship between autistic traits and depression. Positive problem orientation and negative problem-solving style fully mediated the effects of autistic traits on depression. Conclusion: Since people with autistic traits have deficits in problem-solving strategies, they may be vulnerable to symptoms of depression. Increasing the ability of positive problem-solving and decreasing negative problem orientation may serve as a buffer against depression in people with autistic traits.